Feature - Factors Influencing Maize Farmers’ Adoption And Use Intensity of Hermetic Storage Bags In Dormaa, Ghana - Namah Taku-Forchu; Misty D. Lambert; Michael S. Retallick; Jonathan D. Ulmer; George P. Opit (Journal of International Agricultural and Extension Education, 2023)
ABSTRACT Maize is a key staple in Ghana with a high production rate. With the growing development of the poultry and livestock sector, there is a need to boost maize production to meet the growing demand. The unfortunate thing is a significant amount of maize produced is lost during storage. The hermetic storage bag is an innovation proven to reduce maize storage loss. This study ascertains factors influencing smallholder maize farmers' adoption and use intensity of hermetic storage bags in Dormaa, Ghana. We used a multi-stage sampling technique and collected data from 217 maize smallholder farmers from four communities where maize production is the main economic activity in Dormaa Municipality, Ghana. The analytical framework incorporates descriptive statistics, the Probit model, and the Ordinary Least Square Estimation (OLS) technique. The probit results reveal that age, marital status, membership in a professional association, and training have a positive and significant influence on the adoption of hermetic storage bags. Based on the intensity of use of hermetic bags, our study finds that farm size, length of storage, and quantity of maize farmers sold each season had a positive and significant influence on the number of hermetic bags used by farmers to store maize each season. This study provides us with factors development agencies, the Ministry of Food and Agricultural Organization (MoFA) in Ghana, Extension, and other stakeholders should consider disseminating hermetic bags in Dormaa, Ghana to enhance the adoption of hermetic storage bags by smallholder farmers.
Keywords: post-harvest loss; smallholder farmers; adoption; hermetic storage bags; use intensity